(untitled) (Research, Society and Development, 2020)
When we are in the classroom receiving information and teachings from a teacher, we realize that we often do not have information about how these people got there, what were their motivations for their training? What was the trajectory traveled to that classroom? Thinking about these issues, I tried to develop a quantitative research, particularly in Public Educational Institutions; as a recent graduate and administrative technical servant at a federal university, I sought to know from the professors of these institutions, what were their references (professors, friends, relatives, etc.) and decisive factors (financial, empathy, etc.) that made them this teacher to get there. The present work seeks to present and quantify the training percentages of teachers in public Higher Education.